Antioxidants Attenuate Isolation- and L-DOPA-Induced Aggression in Mice - Hira, Sundas; Saleem, Uzma; Anwar, Fareeha; Ahmad, Bashir (Frontiers in Pharmacology, 2018)
Aggression is a major hallmark worldwide attributing negative traits in personality. Wide variety of antioxidants is used for the treatment of many ailments. The present study was conducted to evaluate the role of antioxidants such as ascorbic acid (15.42 & 30.84 mg/kg), beta carotene (1.02 &2.05 mg/kg), vitamin E (2.5 & 5.0mg/kg) & N-acetyl cystiene (102.85 & 205.70mg/kg) in the treatment of aggression. Two aggression models (isolation induced aggression model and L-DOPA induced aggression model) were used in the study. Male albino mice (n = 147) were used in the study which were further subdivided into 11 groups (Group I-control, group II-diseased, group III-standard group, group IV-V treated with ascorbic, group VI-VII treated with beta carotene, group VIII-IX treated with vitamin E, group X-XI treated with N-acetyl cystiene for fourteen consecutive days. Diffrerent biochemical markers (glutathione, superoxide dismutase & catalase) were determined to aevaluate the antioxidant potential in oxidative stress. High dose of vitamin E (5.0mg/kg) was more effective to reduce the aggression in isolated animals while all other antioxidants produced dose-dependent anti-aggressive effect except N-acetyl cystiene which had marked anti-aggressive effect at low dose (102.75mg/kg). Low doses of vitamin E (2.5mg/Kg) & N- acetyl cystiene (102.75mg/kg) and high dose of beta carotene (2.05mg/kg) were effective to prevent all aggression parameters in acute anti-aggressive activity against L-DOPA induced aggression. However all test antioxidants were equally effective in chronic anti-aggressive studies against L-DOPA induced aggression. It may be concluded that selected antioxidants can reverse the aggression which is a key symptom of many neurological disorder.